Perlindungan Hukum Bagi Bank yang Terikat Perjanjian Kerja Sama Penyediaan Fasilitas KPR dengan Skema Perjanjian Buy Back Guarantee Ketika Terjadi Kredit Macet - Amiradiaty Nasution; Andri Noel Hasian Manurung; Benedicta Kesya Anindia (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
In banking practice, cooperation agreements between banks and developers for providing Kredit Pemilikan Rumah (“KPR”) facilities often incorporate the buy back guarantee scheme as a form of security against the risk of debtor default. This scheme obligates the developer to repurchase the property as collateral in case of a loan default. The buy back guarantee scheme in KPR is essential for banks as a risk mitigation mechanism to ensure the recovery of disbursed funds, reduce the potential for non-performing loans, and provide legal certainty and protection against losses caused by debtor default. Therefore, it is necessary to analyze the legal protection available to banks bound by cooperation agreements for the provision of KPR facilities under the buy back guarantee scheme, taking into account the legal position of the banks and developers, as well as examining legal certainty and dispute resolution mechanisms applicable in cases of loan default.